2021
DOI: 10.1007/s11657-021-00932-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with oral bisphosphonates and denosumab among older adults in primary care in Ireland

Abstract: Summary Gaps in pharmacological treatment for osteoporosis can reduce effectiveness. Among older adults, we found about half of new users of oral bisphosphonate and denosumab persisted with their treatment at 2 years, with few switching to alternative therapy. Persistence is suboptimal and warrants evaluation of interventions to improve this. Purpose Gaps in pharmacological treatment for osteoporosis can reduce effectivenes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
8
0
3
Order By: Relevance
“…In our study, the percentage of patients on denosumab increased with time, primarily due to the generally decreasing number of patients still on treatment. The continuous use of BPs and denosumab in older adults was explored in more than one study [ 18 , 19 ]. In 100,000 newly initiated older adults in Canada, the duration of denosumab use was longer than that of BPs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the percentage of patients on denosumab increased with time, primarily due to the generally decreasing number of patients still on treatment. The continuous use of BPs and denosumab in older adults was explored in more than one study [ 18 , 19 ]. In 100,000 newly initiated older adults in Canada, the duration of denosumab use was longer than that of BPs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this particular study, more BP users had discontinued therapy at day 365 (56.7%) than had the denosumab users (33.8%) [ 18 ]. An Irish study including 44 general practices reported 2-year persistence of 49.4% for oral BPs and 53.8% for denosumab [ 19 ]. Of note, less than 10% of the participants had been switched to other medications [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…У пацієнток із захворюваннями печінки запропоновано використання різних ліків від остеопорозу, але більшість досліджень включали невелику кількість пацієнток, що обумовлює відсутність консенсусу з цього питання [8,9].…”
Section: полтавський державний медичний університет українаunclassified
“…Бісфосфонати -антикатаболічні препарати, які збільшують кісткову масу та зменшують частоту переломів при постменопаузальному остеопорозі [10]. Їх вплив на перебіг захворювань печінки на сьогоднішній день не повністю визначений в осно-вному через невелику кількість досліджень та невелику кількість пролікованих пацієнток [5,6,8,9] Для включення в дослідження усім пацієнткам виключали наявність вірусних гепатитів В, С, у дослідження включали пацієнток із нормальними значеннями аланін та аспартатамінторансферази для виключення псевдопозитивної діагностики фіброзу печінки внаслідок ущільнення печінкової тканини на фоні запалення. Усі досліджені пацієнтки знаходились у менопаузі із середнім строком 7,8±3,5 років.…”
Section: полтавський державний медичний університет українаunclassified